2016
DOI: 10.1002/mds.26876
|View full text |Cite
|
Sign up to set email alerts
|

Novel compound heterozygous synaptojanin‐1 mutation causes l‐dopa‐responsive dystonia‐parkinsonism syndrome

Abstract: but preserved repetition and naming. Comprehension was impaired. She was unable to read or write. Verbal memory and visuospatial processing were intact. She exhibited symmetric parkinsonism characterized by rigidity, bradykinesia, resting tremor, and impaired postural reflexes (Supporting Information Video is available online). Brain MRI showed asymmetric frontal atrophy ( Fig. 1A). She reached a state of akinetic mutism at age 69 and died at age 70.Plasma progranulin levels were 27 ng/ml (normal threshold < 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Rauschendorf et al 28 reported two siblings with generalized dystonia. They had the histories of seizure in the childhood.…”
Section: Neurodegenerative Disorder With Involvement Of Dopaminergic mentioning
confidence: 99%
See 3 more Smart Citations
“…Rauschendorf et al 28 reported two siblings with generalized dystonia. They had the histories of seizure in the childhood.…”
Section: Neurodegenerative Disorder With Involvement Of Dopaminergic mentioning
confidence: 99%
“…Several neurodegenerative disorders affecting dopamine system can present with dystonias responsive to dopaminergic drugs. JPD (including SYNJ1 mutation), 24 25 26 27 28 PPS, 29 30 and SCA3 31 are good examples. They have frequent parkinsonism, relatively late onset, and progressive disease course with drug-related complications compared to non-neurodegenerative disorders in the dopaminergic system.…”
Section: Neurodegenerative Disorder With Involvement Of Dopaminergic mentioning
confidence: 99%
See 2 more Smart Citations
“…One of them had reached developmental milestones late, both had cognitive dysfunction in early adult life. CSF analyses showed signs associated with impairments in dopamine synthesis, including decreased homovanillic acid and tetrahydrobiopterin [58]. …”
Section: New Genes For Recessive and X-linked Pd Or Parkinsonismmentioning
confidence: 99%